Bibliophilia in Ottoman Aleppo: Muḥammad al-Taqawī and his Medical Library - Reier, Benedikt (Der Islam, 2021)
Recent research has shown that book collecting by private individuals and institutions was a widespread phenomenon in Bilād al-Shām. At least from the Ayyubid period onwards, countless volumes were produced, changed hands in the book market, and lay around in libraries. To this day, Damascus occupies a central position in our knowledge about libraries and book culture in general, while other cities and regions lag behind. In this article, the inventory of an Aleppine book collector is used to take a glimpse at the book culture of Aleppo in the first decades of the seventeenth century. Although most probably not reflecting the sum total of his library, the inventory still allows to ascertain the specific taste of its compiler, an otherwise unknown Aleppine bibliophile. The inventory also provides evidence for the early distribution of Arabic print and pushes the door open for investigating the role of local agents in the early days of attempts by Orientalists to acquire Arabic manuscripts for European libraries.